Bone Characteristics of 16 Wk-Old-Turkeys Subjected to Different Dietary Supplements and Simulated Stress - Zhou, Z.L.; Rath , N.C.; Huff, G.R.; Huff, W.E.; Rasaputra, K.S.; Salas, C.; Coon, C.N. (International Journal of Poultry Science, 2011)
The effect of two nutritional supplements, a Yeast Extract (YE) and a vitamin D3 formulation (VD) on growth and structural properties of bones from turkeys, transiently subjected to a simulated stress using Dexamethasone (Dex) administration, was determined. The birds were fed diets with or without YE or VD supplements during wks of 6, 11 and 15 post hatch. At weeks 6 and 15 of age, half of the birds in each treatment group received 3 intramuscular injections of Dex at concentrations of 2 mg/kg BW on 3 alternating days to induce simulated stress. At 16 wk of age, the birds were weighed, bled prior to euthanasia and the tibia were harvested at necropsy to determine their mineral content, density and biomechanical properties. Bone Mineral Density (BMD) and Bone Mineral Content (BMC) of whole tibia were determined by Dual Energy X ray Absorptiometry (DEXA) and the biomechanical properties using Instron material testing machine. The ash yield and bone densities were determined using bone marrow free mid diphyseal segments manually by ashing and Archimedes principle. Serum Ca, P, protein and alkaline phosphatase measured using a clinical chemistry analyzer. Neither YE nor VD had any effect on body or bone weights by itself or in combination. Dex reduced both BW and bone weights. DEXA estimated BMD and BMC of whole tibia were reduced in Dex-stressed birds but it was not evident measuring the diaphyseal bone and ash densities. Dex treatment lowered the breaking strength and the plasticity of bone but had no significant effect on its stiffness. Dex treated turkeys showed higher relative bone weights indicating faster recovery of bones from Dex induced growth suppression. Overall, these results suggest that decreased bone mass due to Dex-induced growth suppression reduces bone strength and can alter some structural properties. Intermittent treatment with either VD or YE individually or in combinations do not provide much protection against the negative effects of stress.